Prevalence and antibiotic resistance pattern of bacteria from sepsis suspected neonates at St. Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia - Merema Sherif; Dessie Abera; Kassu Desta (BMC, 2023)
Abstract Background Neonatal sepsis is the major cause of neonatal mortality and morbidity, especially in low and middle-income countries. Continuous monitoring of pathogens and their antibiotic resistance pattern is crucial for managing neonatal sepsis. This study aimed to determine neonatal sepsis due to bacteria, antibiotic resistance patterns, associated risk factors and patient outcomes at St. Paul's Hospital Millennium Medical College. Method An institutional-based cross-sectional study was conducted on 400 neonates suspected of sepsis at St. Paul's Hospital Millennium Medical College from March 2020 to July 2020. A questionnaire was used to collect socio-demographic information, clinical parameters and potential risk factors from study participants. About 2ml of blood was drawn aseptically and inoculated into Tryptone Soya Broth at the patient's bedside. Bacterial identification was performed by using standard microbiological techniques. The disk diffusion method was used to determine the antibiotic susceptibility patterns of each isolated bacteria. Data entry and analysis were done using Statistical Package for Social Sciences (SPSS) version 20 software. Bivariate and multivariable logistic regressions were used to assess associated risk factors of neonatal sepsis. A p-value less than 0.05 was considered statically significant with a 95% confidence interval. Results The overall prevalence of neonatal septicemia was 21% (84/400). Of these, 67 (79.8%) and 17 (20.2%) were gram-negative and gram-positive bacteria, respectively. Klebsiella spp, 37 (44%), E. coli 19 (21.6%) and Coagulase negative Staphylococci 13 (15.47%) were the leading cause of neonatal sepsis. Ciprofloxacin and amikacin were the most effective antibiotics for gram-negative and gram-positive bacteria. Multidrug resistance was observed in 84% of the bacterial isolates. Low birth weight and preterm were associated with neonatal septicemia (AOR = 49.90, 95% CI = 15.14-123.081, P = 0.002) and (AOR = 18.20, 95% CI = 6.835-27.541, P = 0.004) respectively. Conclusion Klebsiella spp and E. coli were frequently isolated bacteria in our study. The proportion of multidrug-resistance was significantly high. Most isolated bacteria were resistant to ampicillin, ceftazidime, cefotaxime and gentamycin, which indicates the necessity of continuous evaluation of antibiotic resistance rate.